The music of the arabs - Touma, Habib (Portland Amadeus Press, 2003)
Encompassing a history of more than 2000 years, the music of the Arabs is unique among the world's various musical cultures. This book presents an overview of Arabic music throughout history and examines the artistic output of contemporary musicians, covering secular and sacred, instrumental and vocal, improvised and composed music. Typical musical structures are elucidated, and a detailed bibliography, a discography (mainly covering the last 50 years) and a guide to the Arabic alphabet for English speakers are also provided. The paperback edition (00331635) includes a CD of seven traditional Arabic pieces performed by contemporary Arab musicians.
Keywords: Ethnomusicology; Music history; Arabia